"Mixed Jew - it's like being half pregnant": Russian-Jewish mixedness in the bureaucratic encounter with the Jewish State1. Issue 2 (3rd July 2017) - Lerner, Julia
ABSTRACT: This article presents an ethnographic picture of Russian immigrants of mixed Jewish origin in their encounter with the state national bureaucracy in Israel. It discusses the meanings and outcomes of the religious categories of classifications embraced by the Jewish state for the newcomers' lived identities. The article suggests that the meanings of ethnic mixture are not given, but that they are constituted in the course of the bureaucratic encounter of migration. Unfolding one ethnographic narrative, I reveal the discrepancy between Israeli citizenship and nationality, expose the contradictions between the Soviet and Israeli perceptions of Jewishness, and interpret the role of religion in the acculturation of Russian-speaking immigrants of mixed Jewish origin.